MORAL PEMERINTAH DALAM MEWUJUDKAN BIROKRASI YANG BAIK (GOOD GAVERNANCE): Studi Kasus Di Desa Japan Kecamatan Sooko Kabupaten Mojokerto - Wijaya, Dian (Universitas Islam Majapahit, Indonesia, 2023)
In providing services to the public, the government is expected to be able to carry out/carry out its duties and authority effectivelywell and not abuse his position and is expected to be able to uphold the values and norms that exist in society, whichusually called Morals. Apparatus/employee discipline is a benchmark in realizing good bureaucracy (Good Gavernance), because the main functionapparatus/employees are to serve the public and also prioritize the public interest rather than their own interests. As isThe morals and code of ethics of Civil Servants can make officers/employees more efficient and responsible for the tasks and authority they are given.to him, the government administration process will also be able to run smoothly if the behavior of the apparatus follows moral values.Based on research results obtained through several informants, government morals can be seen in the implementation of the codeCivil Servant (PNS) ethics with program efforts that can create good conditions. The results of the research prove that qualityand the quantity of human resources possessed by apparatus/employees is still low and is also hampered by several other factors. As isIt is hoped that the programs being implemented will provide an increase in the quality of human resources in the future so that services are betterprovided will run well and the public will feel satisfied with the services provided.